The Effectiveness of the Use of Photosynthesis in Rice Agriculture in Cibiru Hilir Area, Bandung Regency - Supendi, Pipit Iah; Puspita Sari, Putri Nur'aini; Azahra, Siti Fatimah; Salsabil, Zahrina (Jurnal Agrosci, 2025)
For plants, including rice, photosynthesis is an important mechanism for producing biomass and energy. The purpose of this study is to thoroughly examine how well photosynthesis works to increase rice yields in the Cibiru Hilir area, Bandung Regency. This study aims to understand the role of photosynthesis in rice planting techniques by conducting qualitative interviews with resource persons who are farmers in Ibiro Hilir, Bandung Regency. According to the findings of the study, farmers in Lower Cibiru are aware of how important sunlight and water are for the photosynthesis process. They think that improving the quality of rice involves improving the process of photosynthesis through the proper use of sunlight and a good water supply from the mountains.